Virulence determinants of Lactococcus garvieae, an important pathogen of trout - Billenness, Rosemarie (2018)
Lactococcus garvieae is a common pathogen in global aquaculture and has also been isolated as the causative agent of bovine mastitis and in gastrointestinal disorders in humans, where lactococcosis is considered an emerging disease. In aquaculture, the disease manifests with septicaemia, nervous and cutaneous pathology and death in multiple fish species. Outbreaks can cause up to 100% mortality in rainbow trout populations, and the subsequent impact on food production and potential contamination of food for human consumption make devising effective methods to diagnose and control the disease even more important for both human and animal health. Compounding this is the relative lack of knowledge on the virulence factors involved in L. garvieae pathogenesis, its ubiquitous nature in the aquaculture environment and the difficulties involved in differentiating the disease from streptococcal infections with similar clinical manifestations. Pragmatic Insertion Mutant Mapping System (PIMMS) is a transposon insertion sequencing and mapping based strategy which enables identification and comparison of genes which are important for Gram-positive bacterial growth in different environmental conditions using the mutagen pGhost9:ISS1. PIMMS was successfully used to interrogate an L. garvieae 02106 bacterial mutant library to determine which genes were essential for bacterial replication in media and those essential for bacterial growth in fish serum. 398 genes were identified as essential for the growth of L. garvieae after screening in fish serum, the majority involved in bacterial metabolism. Various bioinformatic platforms were employed to further categorise these by functional group and to identify genes with potential involvement in virulence which could form useful vaccination candidates, diagnostic markers or therapeutic targets. Ultimately four genes were identified: divIB, spsB, ancA and the hypothetical protein LAG_00167 which were extracellular or cell-wall associated, conserved amongst other L. garvieae bacterial strains and may provide targets for future targets for therapeutic intervention, prophylaxis or diagnostic test development. Additionally a number of essential metabolic pathways and additional genes of interest were also identified that may also provide alternate control and diagnostic strategies. This study has identified a number of putative virulence factors for L. garvieae infections in the fish host, with the findings relevant to the aquaculture industry, veterinary intervention strategies for fish and cattle health and with potential human food safety implications, where protection of the consumer is paramount in reducing the risk of zoonotic disease.